2017
DOI: 10.3961/jpmph.17.028
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequality in Malnutrition in Under-5 Children in Iran: Evidence From the Multiple Indicator Demographic and Health Survey, 2010

Abstract: ObjectivesThe aim of this study was to assess the socioeconomic inequality in malnutrition in under-5 children in Iran in order to help policymakers reduce such inequality.MethodsData on 8443 under-5 children were extracted from the Iran Multiple Indicator Demographic and Health Survey. The wealth index was used as proxy for socioeconomic status. Socioeconomic inequality in stunting, underweight, and wasting was calculated using the concentration index. The concentration index was calculated for the whole samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…[60]. This finding is similar with results from a cross-sectional study carried out in Mozambique, and Iran [61, 62]. On the other hand, in several countries, the rate of stunting in children living in slums is higher than in the rest of urban areas or rural areas [63].…”
Section: Discussionsupporting
confidence: 79%
“…[60]. This finding is similar with results from a cross-sectional study carried out in Mozambique, and Iran [61, 62]. On the other hand, in several countries, the rate of stunting in children living in slums is higher than in the rest of urban areas or rural areas [63].…”
Section: Discussionsupporting
confidence: 79%
“…The results of this study showed that the prevalence rates of underweight and wasting in Iranian children were 11% and 5%, respectively. However, in another study, the prevalence rates of underweight and wasting were reported to be 5.7% and 3.29%, respectively [ 22 ]. An anthropometric nutritional indicator survey conducted on Iranian preschool children in 1998 reported the underweight and wasting to be 10.8% and 4.9%, respectively [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the prevalence of wasting in the western and central regions is low, in the southern region is high, and in the northern parts of the country and at the national level is scarce. Based on the Millennium Development Goals report published in 2015 [ 22 ], the prevalence of overweight at the national level in Iran is lower than the global prevalence and those in developing countries [ 22 ]. In this study, the subnational division was performed based on the geographical regions and SES of the parts of the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since cultural and behavioral factors can be effective in children's malnutrition and its risk factors (18,19), the results of studies conducted in other countries might not be consistent with our observations in Iran. Because of the high prevalence of childhood malnutrition in Iran (3,20), interventions are necessary for improving child feeding. To establish such interventions, authorities need some information about the problems and risk factors.…”
Section: Introductionmentioning
confidence: 99%